2021
DOI: 10.2106/jbjs.20.01856
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Olecranon Apophyseal Ossification and Sanders Hand Scores with the Timing of Peak Height Velocity in Adolescents

Abstract: Background:The onset of peak height velocity (PHV) guides the timing of interventions in the growing child. The purpose of the present study was to validate the Diméglio olecranon grading system and to compare these scores with the Risser/triradiate closure (TRC), proximal humerus, and Sanders hand scores.Methods:Eighty children with annual serial radiographs were selected from the Bolton-Brush collection. The olecranon apophysis was graded with use of lateral radiographs of the elbow. The mean age to PHV was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…15 Upon validation, it was determined that PHV occurs at stage 5 of this system rather than stage 7 as was originally described, illustrating the importance of using longitudinal datasets when developing skeletal maturity systems. 15 Regardless, the olecranon apophyseal ossification system was found to have utility in identifying risk of progression to a surgical curve ( > 45 degrees) in scoliosis. In a cohort of primarily braced patients, Charles et al 13 found that adolescent idiopathic scoliosis patients at the "half-moon stage" (best correlates with stage 5) with a curve of 21 to 30 degrees had 72.5% chance of progression to a surgical curve, whereas those with a curve of > 30 degrees had 100% chance of progression (Elbow Primer, Supplemental Digital Content 3, http://links.lww.com/BPO/A481; Elbow Practice Radiographs, Supplemental Digital Content 4, http://links.lww.…”
Section: Elbowmentioning
confidence: 80%
See 4 more Smart Citations
“…15 Upon validation, it was determined that PHV occurs at stage 5 of this system rather than stage 7 as was originally described, illustrating the importance of using longitudinal datasets when developing skeletal maturity systems. 15 Regardless, the olecranon apophyseal ossification system was found to have utility in identifying risk of progression to a surgical curve ( > 45 degrees) in scoliosis. In a cohort of primarily braced patients, Charles et al 13 found that adolescent idiopathic scoliosis patients at the "half-moon stage" (best correlates with stage 5) with a curve of 21 to 30 degrees had 72.5% chance of progression to a surgical curve, whereas those with a curve of > 30 degrees had 100% chance of progression (Elbow Primer, Supplemental Digital Content 3, http://links.lww.com/BPO/A481; Elbow Practice Radiographs, Supplemental Digital Content 4, http://links.lww.…”
Section: Elbowmentioning
confidence: 80%
“…To produce its skeletal maturity output, the modified Fels knee system requires the following inputs: chronological age, sex, and evaluation of 7 parameters identifiable on AP knee radiograph (Knee Primer, Supplemental Digital Content 9, http://links.lww.com/BPO/A487; Knee Practice Radiographs, Supplemental Digital Content 10, http://links.lww. 23 Please refer to the supplemental materials for in-depth instruction and examples of how to use this skeletal maturity system. Reprinted with permission from Greene et al 23 Copyright The Journal of Bone and Joint Surgery Inc., Needham, MA.…”
Section: Kneementioning
confidence: 99%
See 3 more Smart Citations